Blue light insertion at night is involved in sleep and arousal-promoting response delays and depressive-like emotion in mice. Issue 3 (26th March 2021) - Wu, Fan; Wu, Shuo; Gui, Qiuqi; Tang, Kaixin; Xu, Qiqi; Tao, Yue; Chen, Meixuan; Cheng, Juan; Wang, Liecheng; Zhang, Lesha
Abstract: Light plays a direct crucial role in the switch between sleep and arousal and the regulation of physiology and behaviour, such as circadian rhythms and emotional change. Artificial lights, which are different from natural light sources with a continuous light spectrum, are composed of three single-colour lights and are increasingly applied in modern society. However, in vivo research on the mechanisms of blue light-regulated sleep and arousal is still insufficient. In this work, we detected the effects of inserting white or blue light for 1 h during the dark period on the wheel-running activity and sucrose preference of C57 mice. The results showed that blue light could induce delays in sleep and arousal-promoting responses. Furthermore, this lighting pattern, including blue light alone, induced depressive-like emotions. The c-fos expression in the blue light group was significantly higher in the arcuate hypothalamic nucleus (Arc) and significantly lower in the cingulate cortex (Cg) and anterior part of the paraventricular thalamic nucleus (PVA) than in the white light group. Compared with the white light group, the phospho-ERK expression in the paraventricular hypothalamic nucleus (PVN) and PVA was lower in the blue light group. These molecular changes indicated that certain brain regions are involved in blue light-induced response processes. This study may provide useful information to explore the specific mechanism of special light-regulated physiological function.